Educational Actions on Drugs in a Research Center: A Rescue History - Costa dos Santos, Pedro Henrique; Faria de Souza, Rayane Cristina; Rodrigues do Amaral, Tatiana; de Siqueira, Marluce Miguel (Guará Journal, 2017)
The Government and Brazilian society are showing more concern conduct prevention and treatment. The current trend includes educational aspects that are grounded in assumptions of health and education. As they allow activities that develop health promotion and education in order to develop actions that can meet the subject in question. Therefore, the involvement of institutionsis necessary, cores and centers to give theoretical support in the campaigns. This study aims to portray the educational activities for capixaba population by Centro de Estudos e Pesquisas sobre o Álcool e outras Drogas - CEPAD in the years 2009 to 2014. It is a descriptive retrospective observational study, developed in CEPAD, located at the Universidade Federal do Espírito Santo - UFES. Using as a data source Relatórios Anuais do CEPAD. As a result, we found that over a period of six years the CEPAD quantified in all 20 educational and 54 educational materials produced. Concluding that the work is important to the educational activities towardssociety to prevent and direct the best approach. It is necessary to encourage educational campaigns that serve as the basis for the health education of society.
Keywords: Drugs; Health education; Prevention